Dysregulation of the IFN‐I signaling pathway by Mycobacterium tuberculosis leads to exacerbation of HIV‐1 infection of macrophages. Issue 5 (19th May 2022) - Dupont, Maeva; Rousset, Stella; Manh, Thien‐Phong Vu; Monard, Sarah Catherine; Pingris, Karine; Souriant, Shanti; Vahlas, Zoï; Velez, Tomàs; Poincloux, Renaud; Maridonneau‐Parini, Isabelle; Neyrolles, Olivier; Lugo‐Villarino, Geanncarlo; et al.
Abstract: While tuberculosis (TB) is a risk factor in HIV‐1‐infected individuals, the mechanisms by which Mycobacterium tuberculosis (Mtb), the agent of TB in humans, worsens HIV‐1 pathogenesis still need to be fully elucidated. Recently, we showed that HIV‐1 infection and spread are exacerbated in macrophages exposed to TB‐associated microenvironments. Transcriptomic analysis of macrophages conditioned with medium of Mtb ‐infected human macrophages (cmMTB) revealed an up‐regulation of the typeI interferon (IFN‐I) pathway, characterized by the overexpression of IFN‐inducible genes. Historically, IFN‐I are well known for their antiviral functions, but our previous work showed that this is not the case in the context of coinfection with HIV‐1. Here, we show that the IFN‐I response signature in cmMTB‐treated macrophages matches the one observed in the blood of active TB patients, and depends on the timing of incubation with cmMTB. This suggests that the timing of macrophage's exposure to IFN‐I can impact their capacity to control HIV‐1 infection. Strikingly, we found that cmMTB‐treated macrophages are hyporesponsive to extrastimulation with exogenous IFN‐I, used to mimic HIV‐1 infection. Yet, depleting STAT1 by gene silencing to block the IFN‐I signaling pathway reduced TB‐induced exacerbation of HIV‐1 infection. Altogether, by aiming to understand why TB‐derived IFN‐I preexposure of macrophages did not induce antiviral immunity against HIV‐1, we demonstrated that these cells are hyporesponsive to exogenous IFN‐I, a phenomenon that prevents macrophage activation against HIV‐1. Graphical Abstract: Here, we identify a mechanism to explain why TB‐derived type I‐IFN is not able to induce antiviral immunity against HIV‐1 in macrophages. Summary: Mycobacterium tuberculosis induces hyporesponsiveness of the IFN‐I signaling pathway in macrophages, leading to the exacerbation of HIV‐1 replication